The Synthesis of Y-zeolite-modified CaCO3-ZnO Nanocomposites as an Antibacterial Agent - Artissiani, Maysa; Widiarti, Nuni; Wahyuni, Sri; Widhihastuti, Endah; Ni'ma, Neli Syahida (Jurnal Kimia Valensi, 2024)
The ability of inorganic antibacterial agents like metal oxides and nanoscale inorganic materials to inhibit bacterial growth rates has yet to receive much research attention. In this study, CaCO3-ZnO/Y-zeolite nanocomposites were created utilizing coprecipitation and impregnation techniques with Ca(CH3COO)2, Zn(CH3COO)2 2H2O, Y-zeolite precursors. Physical and chemical characteristics of nanocomposites have been investigated using XRD, FTIR, and SEM-EDX characterizations. The agar-well diffusion method tested the substance for antibacterial activity against gram-positive and gram-negative bacteria. Nanocomposites have a crystal size range of 35.46-36.53 nm and a crystallinity of 35-37 %, according to the results of XRD analysis. The carbonate groups are visible in FTIR data at wave numbers 1433, 875, and 712 cm-1. The Zn-O absorption band was verified at wave numbers 600-400 cm-1. The Y-zeolite absorption bands at wave numbers 1012-997 cm-1 and 745-746 cm-1 were confirmed. The particle morphology is cube-shaped with irregular sizes. The EDX result showed that the composition consists of 35.92 % calcium, 1.68 % zinc, 44.81 % oxygen, and 13.79 % carbon as elements. With the addition of 2.5 % Y-zeolite, the antibacterial activity of nanocomposites showed the best results, with an inhibition zone diameter of 7.62 mm against Escherichia coli and 6.56 mm against Staphylococcus aureus bacteria.